Análisis funcional y estructural de las proteínas que componen el viroplasma del Virus del Mal de Río Cuarto. Desarrollo de estrategias biotecnológicas para el diagnóstico y control de la enfermedad - Monti, Demián Esteban (2022)
Mal de Río Cuarto virus (MRCV) is a member of the Fijivirus genus of the Reoviridae family that causes the most important maize viral disease in Argentina and is persistently and propagatively transmitted by planthopper vectors. The viral genome consists of 10 segments of dsRNA. In plants, disease symptoms are dwarfism, shortening of internodes, partial sterility and the formation of tumors of phloem tissue in the abaxial veins of the leaves, called enations. Infected plants in late stages of development do not show symptoms. Early in the infection cycle, viral proteins P6 and P9-1 and host proteins form viroplasms. Viroplasms are granular cytoplasmic macrostructures with an electron-dense appearance, which function as viral factories where genomic replication and the assembly of new viral particles occur. P6 and P9-1 interact with themselves and with each other, and P9-1 binds RNA and exhibits ATPase activity. In order to deepen into the structural and functional study of P9-1, the influence of the 24 C-terminal residues (C-arm) of the protein on its ability to multimerize and its functional activities were evaluated. Analysis of the expression of P9-1 and a deletion mutant lacking the C-arm (P9-1?C-arm) fused to GFP in insect and plant cells allowed us to conclude that the presence of the C-arm is necessary for the formation of viroplasm-like structures in vivo. On the other hand, interaction analysis of P9-1 and P9-1?C-arm with nucleic acids indicated that P9-1 has a high affinity for long-chain nucleic acids while P9-1?C-arm has more affinity for short chain nucleic acids. These results allowed us to conclude that the binding capacity to nucleic acids is modulated by protein multimerization. Likewise, the cloning, recombinant expression and purification of P9-1 and P9-1?C-arm carried out in this Thesis allowed the subsequent structural characterization of both proteins by collaborating groups who determined that P9-1 forms decamers and dodecamers in solution while P9-1?C-arm forms dimers. Next, the presence of intrinsically disordered regions (IDRs) in P9-1 was predicted, identifying two IDRs located in the N-terminal region and in the central region. These results partially coincided with what was observed in the crystallographic structure of the protein, where these zones correspond to highly flexible loops. The location of the ATPase site of P9-1 was also predicted using three different methodologies that indicated that the ATP-binding region would be located at the interface between monomers. On the other hand, tools were developed to assist in the study of the viroplasm and the diagnosis of the disease. In particular, a) a library of nanobodies (Nbs)\nobtained from the immunization of a llama with two P6 mutants was biopanned. After performing a phage ELISA, three Nbs directed against P6 were selected and, in a preliminary analysis by Y2H, it was determined that all of them bind to the C-terminal region of the protein; b) the detection of P9-1 and P9-1?C-arm by three selected Nbs (Nb1, Nb13 and Nb25) was characterized by direct ELISA and western blot. It was determined that Nb1 binds to an epitope that is unaffected by the C- arm deletion, Nb13 could target an epitope present in the C-arm or in the final conformation of the entire protein while Nb25 recognizes P9-1 under native conditions and only binds to the reduced and denatured form of P9-1?C-arm. These results indicate that the three characterized Nb are able to recognize different epitopes and versions of P9-1; c) Nbs fusions to fluorescent proteins were engineered and they detected P9-1 in the phloem of infected leaves by confocal microscopy. Fusions of these same Nbs to alkaline phosphatase (AP) were also obtained; d) using the Nb:eGFP and Nb:AP fusions, a sandwich ELISA was developed which showed high diagnostic sensitivity (99.12 %, 95 % CI 95.21 ? 99.98) and specificity (100 %, 95 % CI 96.31 ? 100) and a detection limit of 0.236 ng/mL. In addition, this ELISA was useful for detecting the presence of the virus in insect vectors. Taken together, the results obtained here contribute to the understanding of the molecular mechanisms underlying viroplasm formation and lead to the hypothesis that P9-1 multimerization and the binding of said multimers to viral RNA triggers the liquid-liquid phase separation process giving rise to the formation of early viroplasmas and that this process relies on the presence of the C-arm. The Nbs generated in this Thesis will assist in the study of the MRCV epidemiology, help maize breeding programs, be valuable tools to promote fundamental research on the composition, structure and maturation of the viroplasm and be useful in the development of antiviral strategies.